2. Work in Progress: Workshop Report: Μαντεῖον ἀψευδές. The Sanctuary of Apollo Ptoios in Boeotia: International Workshop on Boeotian Studies organised by Scuola Superiore Meridionale at Naples (13 November 2025) - Mastropietro, Lucrezia, (Teiresias Journal Online, 2025)
Lucrezia MASTROPIETRO (Scuola Superiore Meridionale) Workshop Report: Μαντεῖον ἀψευδές. The Sanctuary of Apollo Ptoios in Boeotia. International Workshop on Boeotian Studies organised by Scuola Superiore Meridionale at Naples (13 November 2025)